Uganda's Recovery : The Role of Farms, Firms, and Government - Reinikka, Ritva; Collier, Paul (Washington, DC: World Bank, 2013)
This book consists of series of studies written by a range of specialists who analyze the responses of private sector agents--households, farms, and firms--and of the government of Uganda itself, to the macroeconomic and structural reforms implemented since the late 1980s in a society recovering from a traumatic civil conflict. The importance of this line of inquiry cannot be underestimated because the success or failure of market-oriented reforms depends crucially on just how private sector agents are able to respond to incentives and opportunities created by the reforms. The analysis in this book draws on quantitative data derived from a series of household surveys and from surveys of firms conducted in the 1990s and more recently in 1999/2000. The household surveys permit analysis of the evolution of income, expenditures, and poverty during this period. The impact of reforms on rural factor markets, on crop and livestock production decisions, and on firms' investment decisions are also among the issues researched in this report. While this report praises Uganda's achievements where warranted, it provides an objective assessment of the reforms and does not shy away from identifying areas where policy mistakes were made. It points out where major weaknesses still exist, notably, public sector corruption, the still poor enforcement of contracts, and the deficiencies in the physical infrastructure.